In silico and in vitro screening of small molecule Inhibitors against SYT-SSX1 fusion protein in synovial sarcoma. (December 2018) - Natarajan, Valliyammai; Ramanathan, Priya; Gopisetty, Gopal; Ramachandran, Balaji; Thangarajan, Rajkumar; Kesavan, Sabitha
Graphical abstract: Highlights: In the present study, 3D structure of SYT-SSX1 fusion protein was generated using threading method. Binding pocket with junction region was identified and grid is generated to carry out docking studies using Schrodinger Suite. Ten compounds were selected using Glide score and ADME properties, of which one promising compound was selected. Cytotoxicity and apoptosis study was carried out for FPTI on synovial sarcoma cell line ASKA which showed the compound could be effective in vitro . Abstract: Synovial sarcoma (SS) is characterized by a tumour specific chromosomal translocation t(X;18) (p11;q11) which results in the formation of SYT-SSX1 fusion protein. This fusion protein represents a clear therapeutic target and molecules specifically targeting SYT-SSX1 fusion protein are currently not available. In this study, SYT-SSX1 fusion protein sequence was retrieved from Uniprot and 3D structure was generated using I-TASSER modeling program. A structure based computational screening approach has been employed using Glide docking software to identify potential SYT-SSX1 small molecule inhibitors that bind to the junction region of the fusion protein. The obtained inhibitors were further filtered based on the docking score and ADME/T properties. Ten best fit compounds were chosen for in vitro studies. The anti-proliferative activities of these 10 compounds were screened in Yamato, ASKA (carries SYT-SSX1 fusion protein) and other sarcoma cell lines such as A673, 143B to understand the specificity of inhibition of the chosen compounds. The in vitro activity was compared against HEK293 cell lines. The compound 5-fluoro-3-(1-phenyl-1H-tetraazol-5-yl)-1H-indole (FPTI) was found to be selectively cytotoxic in synovial sarcoma cell lines (Yamato and ASKA) and this compound also showed insignificant anti proliferative activity on other cell lines. Further, target gene expression study confirmed that FPTI treatment down-regulated SYT-SSX1 and modulated its downstream target genes. Cell cycle analysis revealed the involvement of an apoptotic mechanism of cell death. Further experimental validations may elucidate the therapeutic potentials of FPTI against SYT-SSX1 fusion protein.